Evaluating School Performance: Insights from Teachers and Principals on Teaching and Learning and Teacher Professional Development Quality Indicators - Bicaj, Arberore; Buza, Violeta; Bicaj, Bleona (Journal of Education Culture and Society, 2026)
Aim. This study examines the relationship among teachers' experiences, their assessments of teaching and learning quality, and professional development (PD) in schools. It investigates how internal school assessment policies and quality assurance frameworks impact school performance and teachers' professional development needs, focusing on the Kosovo educational context.Methods. The research utilises a mixed-methods approach, collecting quantitative data from 136 teachers through surveys and qualitative insights from six school principals via interviews. Quantitative analysis involved correlation, ANOVA, and descriptive statistics (SPSS), while qualitative data underwent thematic analysis.Results. Findings indicate that institutional support and quality assurance frameworks shape perceptions of quality, while a gap exists between bureaucratic compliance and instructional innovation. Quantitative data shows no correlation between teachers’ experience and their assessment of quality, suggesting institutional socialisation.Conclusions. The study underscores the need to shift from evaluating policy implementation to fostering peer-driven professional development. Effective school improvement requires context-specific policies beyond a "one-size-fits-all" strategy.